Resident Learning Experience Including Hands-on Model for Procedures With Mammographic Guidance - Jeffrey Brooks (Association of American Medical Colleges, 2014)
Abstract This learning experience for radiology residents features an affordable resident training model that can be used in procedures involving mammographic guidance, such as needle localizations and stereotactic biopsies. This resource contains instructions on creating the model and presentations on how to plan and perform needle localization and stereotactic biopsy, as well as test cases. The model was initially created in order to test a new tool designed to biopsy breast calcifications. As the model was developed, it became clear that it would be excellent for teaching radiology residents the needle localization technique and the stereotactic biopsy procedure without the need for a patient. The model simulates microcalcifications extremely well, using either standard mammography equipment or a stereotactic biopsy table. The model even allows for removal of these simulated calcifications with a stereotactic biopsy system. No other model for these procedures in the literature allows for removal of simulated calcifications.